Sensitive Stripping Determination of Cadmium(II) and Lead(II) on Disposable Graphene Modified Screen‐Printed Electrode. Issue 9 (27th August 2013) - Huangfu, Chao; Fu, Liang; Li, Yuzhi; Li, Xueling; Du, Haijun; Ye, Jianshan
Abstract In the present work, a sensitive, facile and disposable sensing platform for trace analysis of heavy metal ions was developed at the Bi modified graphene‐poly(sodium 4‐styrenesulfonate) composite film screen printed electrode (GR/PSS/Bi/SPE). The GR/PSS/Bi/SPE improved sensitivity and linearity due to the functionalization of graphene with negatively charged PSS providing more absorbing sites. The detection limit of the GR/PSS/Bi/SPE is found to be 0.042 µg L−1 for Cd2+ and 0.089 µg L−1 for Pb2+ with linear responses of Cd2+ and Pb2+ in the range of 0.5–120 µg L−1. Finally, the practical application was confirmed in real water with satisfactory results.